Science Communication in Theory and Practice
XV, 285 p.
Keywords: Hereafter you will find a first: a comprehensive textbook on the communication of sciencein theory and practice! Is there a need for such a textbook? Obviously, yes! Whether you are a scientist, a science journalist, a science teacher, a science museum specialist, a scientific website designer, a science historian, a science entertainer, a member of a scientific society or club, a science tinkerer - there is always a chance that you will be enthusiastic about the job of communicating science, but uncertain about whether you do it well. This book exposes you to the practices of others by reviewing science communication case studies or by inviting you to plunge into the underlying rationale of theoretical approaches to science communication. These are different opportunities for comparing your experience with the practices or reflections of others. The conversation can even be established and furthered with the authors of some of these case studies or of the theories presented in this book by using their website and possibly their email addresses. This book, like a composite, gathers contributions from experts from most of the above mentioned fields. A lot of practices are discussed and they are among the very best practices according to common professional wisdom in the field. Those practices are also reflected upon in an attempt to be somewhat theoretical.